Behavioural Consequences of Risk are Inadequately Embedded in Contemporary Project Management Practice Leading to Sub-optimal Outcomes - Kipp, Michael (Cranfield University, 2017)
3MT presented at the 2017 Defence and Security Doctoral Symposium.The current methodology for the management of projects is driven by a plethora of guidance, techniques and practice often lacking the evidence from successful implementation particularly in projects with significant risk.Causes of project failure are well documented and research indicates there are underlying reasons for failure including a shortage of relevant theory, inadequate skills and insufficient experience. There may also be over-reliance on systematic processes at the expense of behavioural inputs in decision-making when managing risk. Conceivably, there is something important missing from contemporary practice in project management today.Current practice in project management, including traditional, agile and hybrid models, have been analysed to determine the fundamental characteristics of each and the extent to which behavioural factors are embodied. The research concludes, firstly, that agile methods take more account of human factors than traditional techniques and, secondly, that a hybrid approach offers additional benefits in terms of both operational assurance and governance and delivers more favourable outcomes.
Keywords: 'Project'; 'Management'; 'Risk'; 'DSDS17 3MT'; 'DSDS17'; 'Business and Management not elsewhere classified'